Reduction of flatness defects in thin metal sheets by a pure tension leveler. (March 2017) - Mathieu, N.; Potier-Ferry, M.; Zahrouni, H.
Abstract: In metal industries (aluminum, steel, …), the flatness defects of the thin strips can be corrected by pure tension leveling. This process is able to minimize the residual stresses from rolling step by plastically lengthening the metal sheet. This paper introduces a numerical modeling of strip conveying through a simplified industrial leveler (composed of four rolls), using a commercial FEM software. It includes shell elements discretization and frictional contact between strip and rolls. From plastic strains and residual stresses through width and thickness, the final strip shape is predicted. The Finite Element model shows how an entering strip with a flatness defect (manifested or latent) is transformed at the leveler exit: waves are decreased and longitudinal stresses gap is reduced. Abstract : Highlights: A 3D Finite Element model is proposed to simulate a particular configuration of leveling process. The thin metal strip is discretized with shell elements. The model computes stress, strain and plastic strain distribution through strip width and thickness. The final flatness of the strip is predicted. Initial flatness defects are taken into account and corrected by the leveler.